Critico-creative Thinking Pedagogy in ELT - Khadka, Bishnu Kumar (Journal of NELTA Surkhet, 2015)
Teaching and learning English is an energizing, purposeful, and vital experience for developing learners’ competence, confidence, and creativity. It is only possible when we let our learners think critically and creatively in our ELT classroom. This article deals with the theoretical concept of critico-creative thinking as a pedagogy reflecting the practical experiences in general and in ELT in particular. It aims to suggest both teachers and learners to adopt the critico-creative pedagogical strategies while teaching and learning English. Journal of NELTA Surkhet Vol.4 2014: 70-75